2020
DOI: 10.1097/j.jcrs.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol generation through phacoemulsification

Abstract: Purpose: To evaluate whether phacoemulsification is an aerosol-generating procedure in an ex vivo experimental model. Setting: Sussex Eye Hospital, Brighton, United Kingdom. Design: Experimental study. Methods: In this ex vivo study on 15 porcine eyes, an optical particle counter was used to measure particles of 10 µm and less using the cumulative mode based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…To our knowledge, this is the first study to quantify aerosols and droplets levels generated during human vitrectomy surgery in real-world conditions. The results of all 3 experiments are consistent with previous ex vivo vitrectomy and phacoemulsification studies 4 , 5 , 7 demonstrating that although the vitrectomy cutter is a high-speed device, surgery using valved ports is unlikely to generate significant aerosolization. However, when used in open-air conditions inside a gallipot, a vitrectomy cutter may cause a slight increase in particle concentration.…”
supporting
confidence: 85%
“…To our knowledge, this is the first study to quantify aerosols and droplets levels generated during human vitrectomy surgery in real-world conditions. The results of all 3 experiments are consistent with previous ex vivo vitrectomy and phacoemulsification studies 4 , 5 , 7 demonstrating that although the vitrectomy cutter is a high-speed device, surgery using valved ports is unlikely to generate significant aerosolization. However, when used in open-air conditions inside a gallipot, a vitrectomy cutter may cause a slight increase in particle concentration.…”
supporting
confidence: 85%
“…Considering that millions of cataract surgeries are performed in the world each year, these findings carry potential implications for this elective surgery. Assessment of aerosolization during phacoemulsification in ex vivo models suggest that potential spread through the air is likely negligible 10 , 11 but may be dependent on incision size. 12 It is encouraging that there are no known cases of transmission during cataract surgery to date.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosol generation has been evaluated during phacoemulsification and suggestions have been made to minimize visible aerosol production by using a 2.2-mm phacoemulsification tip and reapplying hydroxypropyl methylcellulose (HPMC) coating of the cornea every minute during phacoemulsification [ 38 ]. Another study revealed that phacoemulsification did not generate aerosols of 10 μm or smaller with continuous power using 80% longitudinal, 100% torsional, or 80% longitudinal setting with HPMC on the surface [ 39 ]. Visible aerosol generation during vitrectomy surgery has been also evaluated using a physical model, although this study did not find evidence of visible aerosol generation during simulated vitrectomy surgery [ 40 ].…”
Section: Risk Of Sars-cov-2 Transmission Through Ophthalmic Procedurementioning
confidence: 99%